I've tried everything but therapy. (Part 1) [compact disc] - Swims, Teddy, 1992- (Warner Records, 2023)
Vocal powerhouse Teddy Swims masterfully blends genres from pop, soul, hip-hop, to R&B. With his soul-stirring voice and heartfelt lyrics, Teddy delivers an intimate and cathartic experience, delving into themes of love, loss, and the complexities of life.